Synchrony in parent‐offspring social interactions across development: a cross‐species review of rodents and humans - Ham, Gao Xiang (2023)
In humans, parent-child neural synchrony has been shown to support early communication, social attunement and learning. Further, some animal species (including rodents and bats) are now known to share neural synchrony during certain forms of social behaviour. However, very little is known about the developmental origins and sequelae of neural synchrony, and whether this neural mechanism might play a causal role in the control of social and communicative behaviour across species. Rodent models are optimal for exploring such questions of causality, with a plethora of tools available for both disruption/induction (optogenetics) and even mechanistic dissection of synchrony-induction pathways (in vivo electrical or optical recording of neural activity). However, before the benefits of rodent models for advancing research on parent-infant synchrony can be realised, it is first important to address a gap in understanding the forms of parent-pup synchrony that occur during rodent development, and how these social relationships evolve over time. Accordingly, this review seeks to identify parent-pup social behaviours that could potentially drive or facilitate synchrony and to discuss key differences or limitations when comparing mouse to human models of parent-infant synchrony. Uniquely, our review will focus on parent-pup dyadic social behaviours that have particular analogies to the human context, including instrumental, social interactive and vocal communicative behaviours. This review is intended to serve as a primer on the study of neurobehavioural synchrony across human and rodent dyadic developmental models.